Policy Governance and Performance of County Governments in Kenya - Muriithi, Peter Moffat; Kariuki, Paul; Deya, Jared; Kimani, Ezekiah (Human Resource and Leadership Journal, 2026)
Purpose: The general objective of the study is to examine the influence of policy governance on performance of county governments in Kenya. The study was guided by Systems Theory. Methodology: The study employed a descriptive research design that also employs the quantitative and qualitative approaches due to its in-depth analysis of the influence of administrative governance structures on service delivery in the devolved units in selected county governments in Kenya. The study targeted all the 47 county governments in Kenya. In this study, the unit of analysis was 47 county governments while the unit of observation comprised of 10 County executive committee’s members (CECs) in each county thus making 470 and 47 speakers of the county assemblies hence making a total of 517 respondents. The study’s sample size was reached at using Krejcie and Morgan sample size determination formula. The 220 respondents were chosen with the help of stratified random sampling technique. Structured questionnaires and interview schedule was used in the collection of qualitative and quantitative data. The data collection tools were pilot tested to confirm their reliability and validity. Findings: The study found that policy governance is statistically significant in explaining performance of county governments in Kenya. The influence was found to be positive. This means that unit improvement in policy governance would lead to an increase in p performance of county governments in Kenya. Based on the findings, the study concluded that policy governance positively and significantly influences performance of county governments in Kenya. Unique Contribution to Theory, Policy and Practice: The study therefore recommends that the management of county governments in Kenya should ensure that county policies are evidence-based, inclusive, and regularly reviewed to align with the evolving needs of local communities. This can be achieved by integrating data-driven approaches, such as conducting regular impact assessments and soliciting feedback from citizens, civil society organizations, and experts.